The adoption of blockchain technology in green supply chain networks - Humpert, Diego Andreas Bailon (2020)
The demand for acting sustainable across companies has gained increasing importance. With the goal set by the European Commission to reach a climate neutral economy by 2050,the mission of acting green and lower the carbon footprint will becomea significant challengefor firms across industries.In this paper,a blockchain-based theoretical framework will be proposedas an implementation guidelinefor companies to provide immutable and trusted data towards supply chain partners, customers and thirdparties.As a result, a systematic architecture is introduced reflecting a permission-based distributed ledgerconnected via four additional layersto optimize green supply chain designs and improve transparency.